Development of membrane-targeting TPP+-chloramphenicol conjugates to combat methicillin-resistant staphylococcus aureus (MRSA) infections - Li, Tao; He, Xiaoli; Tao, Wenlan; Zhang, Ruixue; He, Qiaolin; Gong, Hongzhi; Liu, Ye; Luo, Dong; Zhang, Maojie; Zou, Cheng; Zhang, Shao-Lin; He, Yun (European journal of medicinal chemistry, 2024)
Infections caused by drug-resistant bacteria have become a new challenge in infection treatment, gravely endangering public health. Chloramphenicol (CL) is a well-known antibiotic which has lost its efficacy due to bacterial resistance. To address this issue, herein we report the design, synthesis and biological evaluations of novel triphenylphosphonium chloramphenicol conjugates (TPP+-CL). Study results indicated that compounds 39 and 42 possessed remarkable antibacterial effects against clinically isolated methicillin-resistant Staphylococcus aureus (MRSA) with MIC values ranging from 1 to 2 mu g/mL, while CL was inactive to the tested MRSA strains. In addition, these conjugates exhibited rapid bactericidal properties and low toxicity, and did not readily induced bacterial resistance, obviously outperforming the parent drug CL. In a mouse model infected with a clinically isolated MRSA strain, compound 39 at a dose of 20 mg/kg exhibited a comparable or even better in vivo anti-MRSA efficacy than the golden standard drug vancomycin, while no toxicity was observed.